2022
DOI: 10.3390/healthcare10091707
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Study Using Ultrasound to Assess Allowable Needle Insertion Range of Acupoint CV12

Abstract: Background: Abdominal organ injuries are a rarely reported complication when deep acupuncture needling is applied to the abdomen. In order to ascertain the allowable needle insertion range (ANIR) of the abdomen region, we selected acupoint CV12, which is commonly used for treating gastric disease, and ANIR was measured with an ultrasound device. Method: Eighty-five healthy volunteers were recruited, of which 83 cases of ultrasound images were obtained. To investigate the prediction factor of ANIR, we also meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…This study is significant in that it is the first study to analyze the needling depth and anatomical characteristics of acupoint CV23 using ultrasound. In addition, the determination that a characteristic of acupoint CV23 (different from other acupoints) is that it does not show a correlation with BMI or anthropometric factors [3,4]. Therefore, rather than predicting the needling depth according to the patient's BMI for example, without consideration of individual cases, visual observation of the surrounding anatomical structures with ultrasound is expected to contribute to the safe practice of acupuncture procedures.…”
Section: Menmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is significant in that it is the first study to analyze the needling depth and anatomical characteristics of acupoint CV23 using ultrasound. In addition, the determination that a characteristic of acupoint CV23 (different from other acupoints) is that it does not show a correlation with BMI or anthropometric factors [3,4]. Therefore, rather than predicting the needling depth according to the patient's BMI for example, without consideration of individual cases, visual observation of the surrounding anatomical structures with ultrasound is expected to contribute to the safe practice of acupuncture procedures.…”
Section: Menmentioning
confidence: 99%
“…For example, in the case of obesity a high correlation was observed between the use of ultrasound and safe needling practice [1,3]. In a study on acupoint CV12, the liver was observed in 62.7% of the patients' ultrasound images [4]. Therefore, the use of ultrasound for deep needling to acupoint CV12 may prevent organ damage .…”
Section: Introductionmentioning
confidence: 99%
“…. 최근에는 해부용 시신에 초음파를 적용한 연구가 발표되었고 23) , 국내에서도 성인을 대상으로 초음파 및 CT 를 활용하여 연구가 이루어졌다(Table 2) [24][25][26][27] .…”
Section: 복부 경혈의 안전한 자침 깊이 관련 연구unclassified